Socio-Cultural Adjustment and Job Performance Among Expatriates: A Critical Overview - Md Sayed Uddin; Rosazman Hussin; Badariah Ab Rahman (2020)
The significant aspect of the migration process is the adjustment to the socio-cultural as well as work conditions of the host country. Expatriates‟ by and large, come from quite different socio-cultural backgrounds and different work conditions. They are acquainted with different norms and used to different work ethics which have shaped their performance and relations with persons at work. They have to work in a new situation with new personnel and have to adjust to the entire new socio-cultural and working scenarios. It is interesting yet a problematic phenomenon to study their social life, their adjustment to the new socio-cultural milieu, work environment and adoption to innovation in professional arenas. Thus, if the expatriates in one hand can adjust to the situation, they may perform their job well and complete their assignment; otherwise, their stay in the host country will adversely be affected. Thus, socio-cultural adjustment along with innovation adoption is an important phenomenon that affects expatriates‟ stay in the host country, their performance at work and relation with co-workers. The research will carry out using the secondary sources; an overview of existing literatures. It will help to rectify the factors associated to suitable candidates for the organizations/institutions to hire the competent and multiskilled expatriates to host country.